BDNF genotype Val66Met interacts with acute plasma BDNF levels to predict fear extinction and recall. (October 2021) - Ney, Luke John; Matthews, Allison; Nicholson, Emma; Zuj, Daniel; Ken Hsu, Chia Ming; Steward, Trevor; Graham, Bronwyn; Harrison, Ben; Nichols, David; Felmingham, Kim
Abstract: Brain-derived neurotropic factor (BDNF) is a potent regulator of memory processes and is believed to influence the consolidation of fear extinction memories. No previous human study has tested the effect of unstimulated BDNF on fear extinction recall, and no study has tested the association between plasma BDNF levels and psychophysiological responding during an extinction paradigm. We tested the association between fear responses during a 2-day differential conditioning, extinction and extinction recall paradigm and Val66Met genotype in a group of healthy participants ( N  = 191). There were no group differences during habituation or acquisition. Met allele carriers compared to Val homozygotes displayed higher responses to the CS + compared to the CS- during extinction learning and had higher responding to both the CS+ and CS- during extinction recall. Plasma levels of BDNF protein that were collected in a sub-sample of the group ( n  = 56) moderated the effect of Met allele presence, such that lower BDNF level was associated with higher skin conductance response in the Met but not Val group to the CS+ during extinction learning and to both the CS+ and CS- during extinction recall. The current results extend previous observations of a Val66Met effect during fear extinction learning to extinction recall and show for the first time that these effects are moderated by plasma BDNF level. Highlights: BDNF Val66Met genotype is associated with fear extinction efficacy. No study has directly tested whether plasma BDNF moderates this effect. We find Met carriers have poorer extinction and recall. This effect was dependant on plasma BDNF level after extinction learning.